EFEKTIVITAS INSTAGRAM SEBAGAI MEDIA PEMASARAN DI KOPIUNG HAND CRAFTED COFFEE DENPASAR - Juniari, Ni Kadek Eni; Febrianto, I Gusti Agung; Rusdiarnata, I Ketut; Pranadewi, Putu Mira Astuti; Sudiparwati, Putu Ayu (JURNAL BISNIS HOSPITALITI, 2025)
Instagram is a social media application designed for smartphones and functions as a digital communication platform, similar to Twitter. However, its primary distinction lies in its emphasis on photo sharing, allowing users to disseminate visual content within specific contexts or locations. One of Instagram's key advantages is its seamless integration with other platforms under the Meta (formerly Facebook) ecosystem, including WhatsApp, Facebook, and Messenger. Additionally, Instagram offers paid digital advertising features that can be utilized to promote and market products effectively. The objective of this study is to evaluate the effectiveness of Instagram as a marketing tool for KopiUNG Hand Crafted Coffee. This research employs a descriptive qualitative approach, utilizing data collection methods such as interviews, observations, and document analysis. The study is grounded in the theoretical framework proposed by Bambang Dwi Atmoko, which emphasizes four key user engagement indicators: follow, like, comment, and share. The findings indicate that three of the four indicators follow, like, and share have been implemented effectively in the marketing strategy. However, the 'comment' indicator has not yet demonstrated the same level of effectiveness. The outcomes of this study are anticipated to serve as a valuable source of insight and provide strategic recommendations for enhancing the marketing efforts of KopiUNG Hand Crafted Coffee.